2020
DOI: 10.7150/jca.46613
|View full text |Cite
|
Sign up to set email alerts
|

miR-552: an important post-transcriptional regulator that affects human cancer

Abstract: MiR-552 is a small non-coding RNA located on chromosome 1p34.3, and its expression level is significantly up-regulated in tissues or cells of various tumors. miR-552 can target multiple genes. These targeted genes play important regulatory roles in biological processes such as gene transcription and translation, cell cycle progression, cell proliferation, apoptosis, cell migration, and invasion. Besides, miR-552 may affect the efficacy of various anticancer drugs by targeting genes such as TP53 and RUNX3. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 77 publications
2
14
0
Order By: Relevance
“…This miRNA has been shown to be a circulating biomarker of distant metastasis into the lung and the liver (76, 77), it also regulates adenomas via signaling pathways such as MAPK, PTEN/AKT, and STAT (78, 79). In cluster C, we also found a significant targeting role for miR-552-3p, which has been associated with liver cancer and regulates various hallmarks of cancer (80). Supplementary material provides an examination of the relationship between PanomiR miRNAs with DE miRNAs in TP vs NT.…”
Section: Resultsmentioning
confidence: 73%
“…This miRNA has been shown to be a circulating biomarker of distant metastasis into the lung and the liver (76, 77), it also regulates adenomas via signaling pathways such as MAPK, PTEN/AKT, and STAT (78, 79). In cluster C, we also found a significant targeting role for miR-552-3p, which has been associated with liver cancer and regulates various hallmarks of cancer (80). Supplementary material provides an examination of the relationship between PanomiR miRNAs with DE miRNAs in TP vs NT.…”
Section: Resultsmentioning
confidence: 73%
“…The miR-552 is located on chromosome 1p34.3 and encodes a small non-coding RNA involved in post-transcriptional regulation. The two main members of this family are hsa-miR-552-5p and hsa-miR-552-3p, which are highly conserved [11]. miR-552 is significantly overexpressed in several tumor types, where it drives cell proliferation, invasion, migration, and drug resistance, thereby accelerating tumorigenesis [12][13][14].…”
Section: Ivyspringmentioning
confidence: 99%
“…A research-based on RT-PCR, Western blot, and bioinformatics analysis detected for the first time a significant upregulation of miRNA-552 in ovarian malignant tumors [ 113 ]. Their findings suggested that miRNA-552 associated with the PTEN gene (Phosphatase and tensin homolog) can be used for anticipation of the patient prognosis and tumor recurrence [ 113 , 117 ].…”
Section: Biomarkers In the Management And Prognosis Of Ovarian Cancermentioning
confidence: 99%